DO RELIGION AFFILIATIONS CONTRIBUTE TO INVESTOR INVESTING DECISION? A STUDY OF INTERPRETIVE PARADIGMS AND ETHNOGRAPHIC METHODS: DO RELIGION AFFILIATIONS CONTRIBUTE TO INVESTOR INVESTING DECISION? A STUDY OF INTERPRETIVE PARADIGMS AND ETHNOGRAPHIC METHODS - Eliza Fazliyaton Elias; Helma Malini (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tanjungpura, 2020)
ABSTRACT This paper investigated the contribution of religion to an investor investment decision in financial market. A survey involving 150 employees was conducted. The result indicated differences in investment choice decisions between Muslim and non Muslim respondents. There was large number of Muslims who choice stock market to place their fund based on the fatwa that issued by Majelis Ulama Indonesia (Indonesia Muslim council). In contrast, a majority of non Muslims do not have any objection to placed their funding in religion affiliated investment. Religiosity was viewed from a Interpretive paradigms and Ethnographic Methods and accordingly four sets of instruments were used : Descriptive questions, Ethnographic Analytic Interview, Structural questions and Contrast questions. Descriptive questions delivered to find out respondent response to varied questions, Ethnographic questions delivered to find out respondent uniqueness background characteristics and how is it influencing their preferences of investment. The structural questions delivered to find out respondent responses to specific questions on investment. While contrast questions was delivered to find out final decision a contrary choice in investment. The result showed that there is significant contribution from religious affiliation toward investment decision with limited implementation of code of standard and principle of the rules. Keywords: Religion, Investment choice, Investment decision, Indonesia